Answer:
x = -2
Explanation:
First, you need to subtract 2x from both sides. This is because you can't have the same variable (in this case, is x) on 2 different sides, you need to combine them. In this case, you're subtracting since positive (+) 2 and negative (-) 2 will cancel each other out.
3x + 6 = 2x + 4
-2x -2x
_____________
This makes the equation:
x + 6 = 4
Now, all you need to do is subtract 6 from both sides. You're subtracting instead of adding to both sides, because positive (+) 6 and negative (-) 6 cancel each other out.
x + 6 = 4
-6 -6
________
This makes the answer:
x = -2